Organophosphorus Hydrolase-Based Biosensor for Direct Detection of Paraoxon Using Silica-Coated Magnetic Nanoparticles - Khaksarinejad, Reza; Mohsenifar, Afshin; Rahmani-Cherati, Tavoos; Karami, Rezvan; Tabatabaei, Meisam (Applied biochemistry and biotechnology, 2015)
Rapid detection of organophosphorous (OP) compounds such as paraoxon would allow taking immediate decision on efficient decontamination procedures and could prevent further damage and potential casualties. In the present study, a biosensor based on nanomagnet-silica core-shell conjugated to organophosphorous hydrolase (OPH) enzyme was designed for detection of paraoxon. Coumarin1, a competitive inhibitor of the OPH enzyme, was used as a fluorescence-generating molecule. Upon excitation of cumarin1 located at the active site of the enzyme, i.e., OPH, the emitted radiations were intensified due to the mirroring effect of the nanomagnet-silica core-shell conjugated to the enzyme. In presence of paraoxon and consequent competition with the fluorophore in occupying enzyme’s active site, a significant reduction in emitted radiations was observed. This reduction was proportional to paraoxon concentration in the sample. The method worked in the 10- to 250-nM concentration range had a low standard deviation (with a coefficient of variation (CV) of 6–10 %), and the detection limit was as low as 5 × 10⁻⁶ μM.